2019
DOI: 10.1590/fst.32117
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological and physicochemical profiles of the sour cassava starch and bagasse obtained from cassava agroindustry

Abstract: The aim of this work was to evaluate the microbiological and physicochemical qualities of sour cassava starch and cassava bagasse produced during cassava agroindustry in order to evaluate their potential for use in food. All samples were kindly provided by family farmers producers from the region of Cará, in town of Bela Vista de Goiás, Brazil. All of sour cassava starch samples showed microbial counts within the values established by the current legislation. Drying process of raw cassava bagasse to produce th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 31 publications
0
4
0
1
Order By: Relevance
“…Uma das três principais fontes da alimentação humana no mundo, além do arroz e do milho, a mandioca (Manihot esculenta Crantz) é originária da América Latina, onde é cultivada pela população indígena há pelo menos 4000 anos (AKINPELU et al, 2011;MOMBO et al, 2017;GARCIA et al, 2019). A mandioca, pertence à família das Euforbiáceas (RIBEIRO et al, 2012;DE OLIVEIRA et al, 2020), sendo cultivada em mais de 100 países ao redor do mundo (CLAIR, 2017).…”
Section: Introductionunclassified
“…Uma das três principais fontes da alimentação humana no mundo, além do arroz e do milho, a mandioca (Manihot esculenta Crantz) é originária da América Latina, onde é cultivada pela população indígena há pelo menos 4000 anos (AKINPELU et al, 2011;MOMBO et al, 2017;GARCIA et al, 2019). A mandioca, pertence à família das Euforbiáceas (RIBEIRO et al, 2012;DE OLIVEIRA et al, 2020), sendo cultivada em mais de 100 países ao redor do mundo (CLAIR, 2017).…”
Section: Introductionunclassified
“…It has a high potential to be used in biodegradable food packaging sector. It comprises high residual starch content (50%–70%) and high amount of fiber (20%–30%) (Garcia et al., 2019). Moreover, various studies have confirmed the existence of two forms of cassava starch granules (free and bound) within the complex fibrous network, attributing to its residual starch (Farias et al., 2014).…”
Section: Common Approaches Of Different Types Of Biodegradable Materials For Food Packagingmentioning
confidence: 99%
“…Application of agro-industrial waste as alternative biodegradable food packaging matrices would ensure better food security, assure eco-friendliness and help achieving economic benefits through their valorisation [ 24 ]. Cassava (Manihot esculenta) bagasse or cassava pulp is a cassava industrial waste and has been reported to be an excellent source of residual starch and fibre [ 25 ]. Generally, agro-industrial waste cassava bagasse consists of moisture (8.70%), ash (2.15%), protein (1.65%), reducing sugar (0.12), glucose (0.02%), and significantly high residual starch content (47.75%) [ 26 ].…”
Section: Introductionmentioning
confidence: 99%